Crashworthiness study for multi-cell composite filling structures. Issue 1 (2nd January 2018) - Zhang, Yong; Ge, Pingzheng; Lu, Minghao; Lai, Xiongming
ABSTRACT: Lightweight cellular materials such as honeycombs and foams can absorb energy efficiently, and are therefore used as filler materials in thin-walled structures. This paper aims to explore the merits of various filling fashions on the crashworthiness of multi-cell square structures, namely honeycomb filling, foam filling and compound filling of honeycomb and foam. First, finite element models of different filling structures are validated by the theoretical model. Then, the numerical analysis is carried out using nonlinear finite element code LS-DYNA. The results reveal that partially filling the corner cells of the multi-cell square tube using honeycombs (H40) yields best crashworthiness performance. While for foam filling, filling two diagonally opposed corner cells (F20) produces the best results. Finally, the compound filling schemes were implemented, and found that filling the corner cells with honeycombs, and the central cell with foams (H40F01) generates promising crashworthiness performance. Finally, multi-objective particle swarm optimisation algorithm is adopted to maximise the specific energy absorption and minimise peak crushing force of the three novel structures. The results show that partially filling the four corner cells with honeycombs (H40) yields the most desirable crashworthiness performance.